Minority Report on How to End the War in Vietnam (1968)
This Minority Report on "How to End the War in Vietnam" presents an alternative Democratic Party proposal calling for a swift and negotiated end to the conflict. It argues that the war has imposed enormous human and financial costs and rejects escalation, military victory, or unilateral withdrawal as solutions. The report calls for an unconditional halt to the bombing of North Vietnam, followed by negotiations for a phased mutual withdrawal of U.S. and North Vietnamese forces from South Vietnam. It urges political reconciliation in South Vietnam, including negotiations with the National Liberation Front and internationally guaranteed elections, while reducing offensive operations to lower casualties. Finally, it commits to avoiding future "Vietnams" by rejecting unilateral military interventions and emphasizing self-determination, international cooperation, and economic assistance instead of serving as the world's policeman.